Characterization of novel cold-active chitin deacetylase for green production of bioactive chitosan - Mohamed N. Abd El-Ghany; Salwa A. Hamdi; Ahmed K. Zahran; Mustafa A. Abou-Taleb; Abdallah M. Heikel; Muhammed T. Abou El-Kheir; Mohamed G. Farahat (AMB Express)
Abstract A Novel cold-active chitin deacetylase from Shewanella psychrophila WP2 (SpsCDA) was overexpressed in Escherichia coli BL21 and employed for deacetylation of chitin to chitosan. The produced chitosan was characterized, and its antifungal activity was investigated against Fusarium oxysporum. The purified recombinant SpsCDA appeared as a single band on SDS-PAGE at approximately 60 kDa, and its specific activity was 92 U/mg. The optimum temperature and pH of SpsCDA were 15 °C and 8.0, respectively, and the enzyme activity was significantly enhanced in the presence of NaCl. The bioconversion of chitin to chitosan by SpsCDA was accomplished in 72 h, and the chitosan yield was 69.2%. The solubility of chitosan was estimated to be 73.4%, and the degree of deacetylation was 78.1%. The estimated molecular weight of the produced chitosan was 224.7 ± 8.4 kDa with a crystallinity index (CrI) value of 18.75. Moreover, FTIR and XRD spectra revealed the characteristic peaks for enzymatically produced chitosan compared with standard chitosan, indicating their structural similarity. The produced chitosan inhibited spore germination of F. oxysporum with a minimum inhibitory concentration (MIC) of 1.56 mg/mL. The potential antifungal effect of chitosan is attributed to the inhibition of spore germination accompanied by ultrastructural damage of membranes and leakage of cellular components, as evidenced by transmission electron microscopy (TEM), and accumulation of reactive oxygen species (ROS) that was confirmed by fluorescence microscopy. This study shed light on the cold-active chitin deacetylase from S. psychrophila and provides a candidate enzyme for the green preparation of chitosan.